Effect of Mycorrhizal Inoculation (VAM) and Phosphorus Levels on Growth and Yield Attributes of Sunflower (Global Journal of Science Frontier Research, 2018)
to study the effect of my corrhizal inoculation (VAM) and different levels of phosphorus on growth, yield attributes and yield of hybrid sunflower cv. Sunbred. The experiment was conducted by factorial randomized block design with two replications. The treatments of experiment consisted of 5 levels of P 2 O 5 (0, 25, 50, 75 and 100kg/ha) applied in the presence or absence of VAM inoculates. The results revealed that growth, yield attributes and yield was significantly influenced by various P levels in the presence and absence of VAM inoculations. The growth and yield of sunflower was highest under mycorrhizal inoculated plants than non micorhizal inoculation. Among the various phosphorus levels tried, P 2 O 5 at 100 kg ha-1 recorded maximum values for growth and yield, while P 2 O 5 at 0kgha-1 registered minimum values for growth and yield of sunflower. Among the treatment combinations tried, mycorrhizal inoculation with P 2 O 5 @ 100 kg ha-1 recorded maximum values for growth and yield attributes and yield of sunflower (2153 kgha-1 ) but it was on par with M 2 P 3 (mycorrhizal inoculation with P 2 O 5 @ 75 kg ha-1 ). The lowest values of growth and yield attributes and yield were recorded by non-mycorrhizal inoculation with P 2 O 5 @ 0 kg ha-1 .
Keywords: sunflower; VAM growth and yield